O princípio constitucional do desenvolvimento e a utilização de recursos hídricos na indústria de petróleo - Galvão, Rafael Silva Paes Pires (2008)
As can be inferred by the title of its study The constitutional principle of sustainable development and the utilization of hidrical resources in the oil industry the transcribed pages are dedicated to the approach of the mentioned subjects which, despite being apparently different, will be shown intrinsically connected as goes by the study. The superation of this first step by the reader will lead to an important perception of the title: that the situation requires, urgently, a defined posture, a complete conduct change and, therefore, a modification of the paradigms currently establisheds. To brake barriers, modifying what is lived by, is the ultimate goal. For that, there is no unique path, linear, but there were broached the development themes, the hidrical resources theme and oil and natural gas industry at the necessary points to achieve, by the end, a comprehension for the Brazilian Federal Republic goals in the search for the application of these juridical norms. The ones whom lay down over this study shall notice that, more than a simple approach over these themes (which are still less worked and searched in Brazil), the heavy critic of an instituted and pacifically accepted reality, directly offensive of the constitutional principles. The debate evolves from punctual and specific aspects, it gains life, flies, searching how the juridical order equalizes the economic model to the environment defense. Standing by the possibility of conciliation among constitutional principles, the remodeling of an economic segment is defended, aligning it to the sustainable limits. Development, sustainable, becomes means and goals to the implementation of liberty, capacitating everyone to achieve their goals of life, their libertments, fruit of the inherent antagonism of the Constitution the sustainable development offers, while an axiological vector, a new reality to the economic order, turning it into a motriz element to the fortification of constitutional normative force and for the national development